Understanding the Concept of Rulership According to al-Ghazali in Nasīhat Al-Mulūk and Machiavelli in The Prince: A Comparative Analysis - Nur Adillah Omar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The objective of this study is to analyse the concept of rulership according to the perspectives of two scholars from the area of political philosophy, namely al-Ghazali and Machiavelli. It is important to fully understand the concept of rulership according to these two scholars as presented in their books Nasīhat al-Mulūk and The Prince in order to know the basis of political systems advocated by al-Ghazali and Machiavelli in relation to the advice they gave to their respective rulers in ruling the states during their time. It is necessary to research on this since their respective views on rulership are not only for the people who lived in the past, but also for the present and future generations. Of course, both scholars have contradictory views. Al-Ghazali upholds religion as the foundation of his political approach, whereas Machiavelli is a secular thinker, who detaches religion and morality for the foundation of his political approach. However, both scholars use the same framework of political system, which is the authoritarian political system framework, in giving advice to the rulers in governing their states. Thus, this thesis analyses the concept of rulership in order to justify the authoritarian style of political system that has been theorised by both al-Ghazali and Machiavelli, based on Nasīhat al-Mulūk and The Prince respectively using Juan Linz’s framework of authoritarian political system which are 1) limited pluralism, 2) mentally, 3) mobilization and 4) leadership.I used qualitative methodology, which is library research and content analysis in analysing the concept. In conclusion, based on the books, Nasīhat al-Mulūk by al-Ghazali and The Prince by Machiavelli, both scholars advocated authoritarian political system in giving advice to the rulers.